Experiment on Heat Exchanger Using Innovative Coils and Phase Change Material/MXene Nanofluids - Sarkar J.; Sahoo R.R. (My University, 2025)
The utilization of innovative coiled wire turbulators along with phase change material (PCM; improving heat capacity) or MXene (having good dispersion stability) dispersed nanofluid in tubular heat exchangers may boost performance; however, it has not been explored yet. In the current analysis, experimental research is done on various mono-nanofluids and hybrid nanofluids flowing in a double-pipe heat exchanger with tapered, coiled wire turbulators to examine the hydrothermal aspects. Four coiled wire turbulators (conventional helical, conversing tapered, diverging tapered, and converging–diverging tapered) and four nanofluids (Al2O3∕water, PCM/water, Al2O3 PCM∕water and MXene/water) are utilized in the heat exchanger with all possible combinations. The effects of fluid types, turbulator types, total nanoparticle volumetric fraction, and nanofluid volume flow rate are investigated. Two thermal parameters (heat transport coefficient and Nusselt number), two hydraulic parameters (drop of pressure and friction coefficient), and two hydrothermal parameters (ratio of heat transport coefficient and drop of pressure, and generation of entropy) are considered objective functions. The study reveals that the diverging tapered, coiled wire yields significantly higher performance as compared to the conventional helical coiled wire as an insert. MXene/water has higher thermal performance; however, PCM-dispersed hybrid nanofluid yields better hydrothermal performance than other studied fluids. © 2024 by the American Institute of Aeronautics and Astronautics, Inc. All rights reserved.